PIJAT REFLEKSI BERPENGARUH TERHADAP TEKANAN DARAH PADA PASIEN HIPERTENSI DI KLINIK ATGF 8 PALEMBANG - Lukman Lukman; Sumitro Adi Putra; Elba Habiburrahma; Sukma Wicaturatmashudi; Rumentalia Sulistini; Ismar Agustin (Poltekkes Kemenkes Jambi, 2020)
Background: Hypertension is often referred to as an unknown killer, because patients do not know that they suffer from hypertension. Many types of complementary therapies that can be applied to treat hypertensive patients, one of which is reflexology Method: This study aims to determine the effect of reflection on blood pressure in hypertensive patients at the Palembang ATFG-8 clinic. The design used in this study was pre-experimental using one group pre-test post-test design. The sample in this study were all hypertensive patients who visited for reflexology in April 17 until May 17, 2018. Determination of the sample using a purposive sampling method totaling 18 subjects. Result: The results obtained were the average age of the sample 54.22 years (± 7.216), systolic blood pressure before 148.44 mmHg (± 4,527) and after reflexology 143.78 mmHg (± 8,633). Diastolic blood pressure before 95.72 mmHg (± 2.886) and after reflexology 91.06 mmHg (± 5,252). The paired sample T test results showed the effect of reflexology on systolic blood pressure (p = 0.026) and diastolic (p = 0.001). Conclusion : There was a decrease in blood pressure statistically, but in substance it was not significant. The next researcher is expected to carry out further research by adding samples and using a control group.